Validation of Indonesian Brief Measurement of Religious Coping (Brief R Cope BI) - Mulyono, Wastu Adi; Ekowati, Wahyu (Jurnal Keperawatan Soedirman, 2023)
Religion and spirituality are determinants of psychological adjustment of coping resources, especially in a religious country such as Indonesia. However, in general, its measurement does not use standardized scales. This study aimed to examine the validity of the Indonesian version of the Brief Measurement of Religious Coping (Brief RCOPE). The sample of this study was 150 women recruited by a consecutive sampling strategy. Exploratory factor analyses were performed to examine the structure’s validity. The criteria’s validity was measured by its correlation with the Freiburg Mindfulness Inventory and FACIT Sp12. The exploratory factor analyses indicated that the Indonesian Brief RCOPE satisfied the construct validity. The Bartlett sphericity test was significant (df (91) = 1109.79, p < 0.001), and the Kaiser-Meyer-Olkin (KMO) test was 0.782. The exploratory factor analyses confirmed that the two-factor design model with 50.4% explained the variance. Positive religious coping was correlated with mindfulness (r = 0.338, p < 0.01) and spirituality (r = 0.317, p< 0.01), while negative religious coping was correlated with perceived stress (0.182, p < 0.05). Cronbach’s alpha coefficients for Factor 1 and Factor 2 were 0.83 and 0.82, respectively. Thus, the Indonesian version of Brief RCOPE is valid and reliable for measuring positive and negative religious coping.